Pengaruh Variasi Jumlah Tumbukan Pada Perkerasan Hrs-Wc Dengan Metode Marshall Test - Sainuddin, Sainuddin (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2024)
Roads are one of the transportation infrastructures that are really needed for daily life, so during their service period it is hoped that the condition of the road will be durable according to its intended lifespan. One of the influences that makes an asphalt mixture good is the compaction carried out during implementation. The compaction assessment is expected to determine the density and strength of the asphalt layer through the marshall limit to obtain the ideal strength value for the asphalt mixture, so it is important to know the ideal number of collisions during implementation. . The results of tests on the effect of variations in the number of collisions on marshall characteristics that have been carried out produce values ​​that meet the specifications set by SNI Bina Marga 2018 revision 2, including tests that obtained a stability value of 2086.99kg, a flow value of 3.55 mm, a VIM value of 5.84% , the VMA value is 18.69%, the VFB value is 68.73%, and the MQ value is 587.89 kg/mm, so that an optimum collision of 60 collisions is obtained. Thus it can be stated that it meets the HRS-WC specifications.